Is Only Clarithromycin Susceptibility Important for the Successful Eradication of Helicobacter pylori? - Kim, Young Min (Antibiotics (Basel), 2020)
Resistance to clarithromycin and other antibiotics included in the eradication regimen, such as amoxicillin and metronidazole, is important for Helicobacter pylori (H. pylori) eradication. The aim of this study was to investigate the correlation between the results of antimicrobial susceptibility testing and the eradication rate, as well as to understand the importance of antimicrobial susceptibility testing in H. pylori eradication. We retrospectively reviewed the electronic medical records of 1862 patients who underwent gastric biopsy for the culture of H. pylori during upper endoscopy from March 2015 to June 2019. We tried to find a correlation between the results of the antimicrobial susceptibility testing and the eradication rate in patients who received standard triple or concomitant therapy. A total of 247 patients exhibited positive results for culture and underwent antimicrobial susceptibility testing. Of these, 146 received eradication therapy, with follow-up tests after treatment. In the standard triple therapy, patients who were susceptible to both clarithromycin and amoxicillin exhibited significantly higher eradication rates (85.9%) than those susceptible to clarithromycin and resistant to amoxicillin (75.0%) or those resistant to clarithromycin and susceptible to amoxicillin (44.4%) (p = 0.013). In the concomitant therapy, patients who were susceptible to both clarithromycin and metronidazole had significantly higher eradication rates (96.3%) than those susceptible to clarithromycin and resistant to metronidazole (88.9%) or those resistant to clarithromycin and susceptible to metronidazole (50.0%) (p = 0.016). There was a correlation between the results of antimicrobial susceptibility testing and the eradication rate for H. pylori. In addition to clarithromycin, susceptibility to amoxicillin and metronidazole is also important for the successful eradication of H. pylori.